Collaboration of ministries/institutions and the private sector in handling cyber threats through the establishment of Computer Security Incident Response Team (CSIRT) - Rohman, Husni; Sumarna, Sumarna; Suwanda, Suwanda; Leksmanawati, Widya (Technium Social Sciences Journal, 2022)
The writing of this article aims to describe how the coordination efforts of Ministries / Institutions and the Private Sector in handling cyber threats through the formation of a Computer Securtiy Incident Response Team (CSIRT). The research method used is a qualitative method through the study of literature from various reference sources and other documents. The writing of this article is descriptive and explanatory to obtain facts and describe a comparative analysis of cyber threat handling policies through CSIRT in various countries with Indonesia. The secondary data used are obtained not from direct observation but rather obtained from several previous studies such as research reports and other important documents. The result of this research is how collaboration is carried out by Ministries/Institutions and the Private Sector in handling cyber threats through the formation of a Cyber Incident Response Team organization.